Homeschool Student Physical Activity Compared to Public/Private School Students: The 2017 US National Household Travel Survey. (25th March 2021) - Tribby, Calvin P.; Berrigan, David
ABSTRACT: BACKGROUND: School is an important place for physical activity (PA); however, little is known about how homeschool students' PA levels compare with public and private school students. This study estimated the national prevalence of PA levels of homeschool students compared to public and private school students. METHODS: We used the 2017 National Household Travel Survey for school‐aged participants (N = 31, 486) to compare weekly PA (not active, light or moderate activity, or vigorous activity) by school type (public/private or homeschool) and school level (elementary, middle, and high school). RESULTS: Unadjusted analyses found higher prevalence of physical inactivity for homeschool students, 14.2% (95% CI, 9.7‐18.7%), compared to public/private school students, 8.0% (95% CI, 7.1‐9.0%). For students who reported any PA, there was no difference in mean number of episodes for light or moderate PA [public/private: 4.2 (95%, CI, 4.1‐4.3), homeschool: 4.3 (95% CI, 3.9‐4.6)], or vigorous PA [public/private: 5.6 (95% CI, 5.5‐5.7); homeschool: 5.5 (95% CI, 4.9‐6.0)]. Results were comparable for covariate‐adjusted analyses. CONCLUSIONS: A higher percentage of homeschool students report being physically inactive compared to public/private school students. However, data with more specific measures of PA intensity and duration are required to determine the potential magnitude of reported differences in behavior.